2022
DOI: 10.3390/pathogens11010062
|View full text |Cite
|
Sign up to set email alerts
|

News Insights into the Host-Parasite Interactions of Amyloodiniosis in European Sea Bass: A Multi-Modal Approach

Abstract: Amyloodiniosis is a disease resulting from infestation by the ectoparasitic dinoflagellate Amyloodinium ocellatum (AO) and is a threat for fish species such as European sea bass (ESB, Dicentrarchus labrax), which are farmed in lagoon and land-based rearing sites. During the summer, when temperatures are highest, mortality rates can reach 100%, with serious impacts for the aquaculture industry. As no effective licensed therapies currently exist, this study was undertaken to improve knowledge of the biology of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A. ocellatum is among the most pathogenic ectoparasites, causing major economic losses in brackish and marine fish aquaculture (Kuperman & Matey, 1999; Francis‐floyd & Floyd, 2011). There is, however, a scarcity of verified evidence on the pathogenesis of amyloodiniosis, and preventive strategies are limited (Lieke et al., 2020; Massimo et al., 2022). The present investigation established an in vitro platform as a proxy for investigating A.ocellatum ‐host interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A. ocellatum is among the most pathogenic ectoparasites, causing major economic losses in brackish and marine fish aquaculture (Kuperman & Matey, 1999; Francis‐floyd & Floyd, 2011). There is, however, a scarcity of verified evidence on the pathogenesis of amyloodiniosis, and preventive strategies are limited (Lieke et al., 2020; Massimo et al., 2022). The present investigation established an in vitro platform as a proxy for investigating A.ocellatum ‐host interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloodiniosis is a ‘quiet’ disease; the host displays no clinical symptoms following infection of a small number of trophonts, but due to the rapid proliferation of A. ocellatum , the fish do not respond to therapy by the time of fish showing signs of disease as it is already too late (Soares et al., 2011). Several studies that investigated the effects of A. ocellatum infection on the host linked fish mortality to inflammation, osmoregulatory disturbances and secondary microbial infections due to severe epithelial damage (Massimo et al., 2022; Moreira et al., 2017, 2018, 2019). Histopathological examination of infected fish gills revealed epithelial cell hyperplasia and hypertrophy of the lamellae, as well as fusion of secondary lamellae, telangiectasia and mucous cell proliferation, culminating in disintegration and necrosis of the lamellar structure of the gill (Noga, 2012; Nozzi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasm of the epithelial cells damaged by the parasite that are consequently detached stained iNOS + , but interestingly, iNOS was also produced abundantly within the parasite's cell. Such antibody recognition of a highly conserved iNOS epitope within the parasite tissues is potentially related to a high metabolic rate of cells during active parasitation, as observed in dinoflagellate A. ocellatum infecting the European seabass gills and oropharyngeal cavity 113 …”
Section: Pathologymentioning
confidence: 98%
“…Regarding the primary sites for A. ocellatum dinospore fixation, it is widely accepted that skin and gills are the main infected organs. 65,120 Most recently it was also reported that the oropharyngeal cavity 163 and the eyes 155 of fishes are also primary sites of infestation. Additionally, Rand and Wiles 164 observed A. ocellatum trophonts attached to muscle tissue on reef silverside (Atherina harringtonensis).…”
Section: Host-parasite Interactions In a Ocellatum Infestations 41 | ...mentioning
confidence: 99%